Ion exchange resin selection for concentration and purification of uranium leached by sulphuric acid solution - Le , Quang Thai; Pham , Minh Tuan; Trinh , Nguyen Quynh; Vu , Khac Tuan; Nguyen , Hong Ha; Bui , Thi Bay (Nuclear Science and Technology, 2015)
Ion exchange is one of the most popular techniques for recovery and purification of uranium from sulfuric acid leaching solution, especially for recovery of uranium from a low uranium containing solutions. Resins commonly used are strong base or weak base anion resins with amine functional group. The anionic form of resins may be NO3-, Cl- , SO42- or OH-. The selection of a resin depends on the uranium total exchange capacity, selectivity and the cost. The previous studies often use Amberlite IRA-420 for concentration and purification of uranium solution from Pa Lua sandstone ores. This is a good and suitable resin but high price. To diversify the resins and reduce the costs, instead of IRA-420, the authors tested two commercial resins Indion GS300 (India) and Purolite A400 (UK) in the processing of uranium solution from sandstone ores. The results showed that the uranium total exchange capacity of these resins is only about 80 - 85% over Amberlite IRA-420, but these resins should be able to be used instead of Amberlite IRA-420 due to their low cost and availability in Vietnam.